"Time series momentum" in commodity markets. Issue 7 (3rd June 2014) - Chevallier, Julien; Ielpo, Florian
Abstract : Purpose: – The purpose of this paper is to contain an empirical application of the concept of "time series momentum" – as developed by Moskowitz et al. (2012) – to commodity markets with daily data during 1995-2012. Design/methodology/approach: – The paper applies the new concept of "time series momentum" to the sphere of commodity markets. Findings: – The paper extends the results previously obtained by Moskowitz et al. (2012) to a second category labeled "breakout strategy." Research limitations/implications: – Further management strategies can be elaborated for investment management purposes, based on the suggested inclusion of the "time series momentum" in commodities. Practical implications: – The empirical evidence gathered in this paper bears practical significance for portfolio managers and commodity tradings advisors relying on trend following strategies. Originality/value: – Commodity markets are quickly developing to an alternative asset class for investors. Discovering their properties and characteristics has a broad appeal in finance.